Validation study of a non-invasive diagnostic device for lipid profile / Nurul Asyiqin Mansor - Nurul Asyiqin, Mansor (2019)
To design and develop a new medical device, a manufacturer must conduct clinical testing on the human subject to test the effectiveness and safety aspect of their newly developed device. In addition, to enable the device to be produced in large mass in the respective country, the manufacturer as well as local representative (if overseas made) must register their device to the authority. Thus, as a part of the registration procedure, a validation study needs to carry out in order to confirm the effectiveness of the device in performing the intended function. Therefore, this study is carried out to validate a new medical device that based on bioimpedance analysis (BIA) principle in estimating lipid profile parameter in diseases through a non-invasive procedure. The objective of the study is to find an association of the new medical device parameter and the lipid profile in subject attending primary care setting. A random group of adult patients was chosen based on the lipid profile form. The 48 subjects were recruited on the test day. Anthropometry measurement, the BIA-based medical device and lipid test measurement were taken on the same day. The subjects were then classified according to lipid profile parameter accordingly. The independent t-test and multiple logistic regression were used for data analysis. Based on the statistical analysis the result showed that the impedance (5,100,200